What To Expect In An Unexpected Spontaneous Bilateral Ectopia Lentis: Poster Presentation - Case Report - General practitioner - Yudakusuma, Cheryll; Susyono, Maria Larasati (Majalah Oftalmologi Indonesia, 2023)
Introduction : Ectopia lentis is present in 50% to 80% of Marfan syndrome sufferers. In many people the position of lens is fixed, some individuals’ lens experience subluxation which took amount of time. This case presents a young patient with rare manifestation of spontaneous bilateral ectopia lentis, both lens luxated within two days after admission due to secondary glaucoma. Case Illustration : A 14 years old patient came to the emergency department with acute glaucoma like symptoms: pain and redness in both eyes, along with headache and nausea. The patient appeared highly suspectedof Marfan syndrome appearance with tall stature, and arachnodactyly; both eyes shown visual acuityof 1/300, low digital palpation, ectopia lentis and anteriorly subluxated lens in both eyes, positive fundus reflex. Posterior segment USG B-scan is normal. Patient then prescribed with oral Acetazolamide, Timolol Maleate eye drop, and Prednisolone eye drop, then scheduled for lensectomy. Just within 2 days after admission, right eye shown lens anteriorly luxated with 20/100 visual acuity, while left eye appears aphakic with ectopia lentis at vitreous with 1/60 visual acuity. The physician immediately sent the patient to higher referral hospital then received secondary implant on right eye and secondary implant with vitrectomy procedure on left eye. Discussion : Drastic measure took place given the presence of both lenses' dislocation, one into anterior chamber, another into vitreous cavity. Collaboration with cardiologist is necessary to perceived other potential comorbid. Conclusion : Physician do need always to be prepared for even the uncommon complications to occur, hence have to be prepared for the unexpected.